Parents' Understanding Of Children At Risk Of Stunting (Case Study of RW 03 Karangbesuki Village, Sukun District, Malang City) - Azzahra, Patimah; Hardika, Hardika; Rahma, Rezka Arina (Universitas Negeri Malang, 2024)
The aim of the research is to find out and describe parents' understanding of stunting, provide parents with understanding about stunting, and the response given by parents after getting an understanding of stunting from posyandu cadres. This research uses qualitative research with a case study approach. The data collection techniques used in this research are interviews, observation and documentation. Based on research that has been conducted, the research results obtained are that almost all parents have sufficient understanding about stunting, especially parents who have children at risk of stunting. Providing this understanding is carried out by posyandu cadres during the implementation of posyandu activities, by providing outreach and counseling to parents who have children at risk of stunting, routine supplementary food (PMT) is given to children at risk of stunting, and the response given by parents after gaining understanding is also very good, almost the majority of parents already understand and are starting to be aware of stunting and its dangers to children's health in the long term. Keywords: Parental understanding, Stunting